Functional Teacher Education and the Role of Islamic Studies Teacher in Promoting Holistic Development in the 21st Century - Wasilat Adigun (Journal of Islamic Studies and Education, 2025)
Functional teacher education equips educators with the skills, competencies, and professional values required to address the educational and societal demands of the 21st century. Despite Islam’s emphasis on knowledge acquisition and character formation, many Islamic Studies teachers in Nigerian schools and teacher-training institutions remain insufficiently prepared for contemporary challenges. Key constraints include outdated curricula, shortages of professionally trained teachers, limited integration of digital pedagogical tools, and weak in-service professional development systems. These shortcomings restrict the potential of Islamic Studies to contribute meaningfully to national development, social cohesion, and the cultivation of critical thinking skills essential for modern learners. In the context of rapid social change, technological advancement, and rising youth unemployment, the gap between current instructional practices and societal needs has widened, highlighting the urgency for reform in Islamic Studies teacher education. This study examines the role of Islamic Studies teachers in promoting students’ holistic development moral, spiritual, cognitive, and socio-economic through the integration of functional teacher education with Islamic pedagogical principles. Using a descriptive research design, data were collected from 270 respondents in Kwara State, Nigeria, and analyzed thematically. The findings suggest that strengthening Islamic Studies teacher education through functional approaches and continuous pedagogical support can enhance the subject’s relevance and contribution to moral rejuvenation, socio-economic resilience, and sustainable national development.